Analysis of the risks of the spread of camelpox in Kazakhstan (Eurasian Journal of Ecology, 2022)
Camel breeding is an important area of domestic animal husbandry. Significant territories of Kazakhstan are occupied by deserts, and camels are one of the few domestic animals capable of living on such lands. Camelpox is the most economically important viral callus disease of camelids. Previously, epizootics of this infection occurred in the country. It is important that the number of camels in the country has been constantly increasing over the past decade, so the risks associated with the emergence of new epizootics are multiplying. To ensure effective measures to control this dangerous disease of camels, it is necessary to carry out total monitoring of the entire territory of the country. Sporadic serological studies were previously carried out only in the Mangystau region, the level of seroprevalence to the camelpox pathogen for other regions of the country has not been determined. It is critical that such monitoring is carried out before the start of the camel vaccination campaign with a domestically produced vaccine, so that the effectiveness of the vaccination can be assessed. The article presents data on the analysis of risks associated with the spread of camelpox in Kazakhstan, as well as the results of preparatory work for monitoring the country's territory in relation to camelpox.Key words: camelpox, camelpox virus, Orthopoxvirus, epizootology, epidemiology.